2015
DOI: 10.1007/s11203-015-9123-z
|View full text |Cite
|
Sign up to set email alerts
|

Modified Schwarz and Hannan–Quinn information criteria for weak VARMA models

Abstract: Numerous multivariate time series admit weak vector autoregressive movingaverage (VARMA) representations, in which the errors are uncorrelated but not necessarily independent nor martingale differences. These models are called weak VARMA by opposition to the standard VARMA models, also called strong VARMA models, in which the error terms are supposed to be independent and identically distributed (iid). This article considers the problem of order selection of the weak VARMA models by using the information crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…We also presented statistical information about the Schwarz criterion (it is a criterion for model selection among a finite set of models), Hannan-Quinn criterion (it is an alternative to the Akaike information criterion) and Durbin-Watson (statistic to detect the presence of autocorrelation at lag 1 in the residuals). This statistical information is according to Maïnassara and Kokonendji (2016).…”
Section: Results Presentation and Analysismentioning
confidence: 99%
“…We also presented statistical information about the Schwarz criterion (it is a criterion for model selection among a finite set of models), Hannan-Quinn criterion (it is an alternative to the Akaike information criterion) and Durbin-Watson (statistic to detect the presence of autocorrelation at lag 1 in the residuals). This statistical information is according to Maïnassara and Kokonendji (2016).…”
Section: Results Presentation and Analysismentioning
confidence: 99%
“…Among the three measures, it is reported that the SBC can perform better when dealing with high-dimensional dataset, as presented the proposed SBC index has provided the lowest lag, while the AIC index has resulted in the largest lag among all three criteria [34]. In addition, HQC has offered an average lag in comparison with the SBC and AIC indexes [33,37]. To determine the lag length, the Schwarz-Bayesian model has been used to obliterate the correlation between the residual.…”
Section: Statistical Specification Variablesmentioning
confidence: 93%
“…Determining optimal dependent variables for regression and elimination of the correlation between disturbance terms, among all three criteria (AIC, SBC, and HQC), see [34][35][36][37]. It is likely to obtain different lags which can result in uncommon answers.…”
Section: Determining the Optimal Lagmentioning
confidence: 99%
“…We checked the quality assessment of ARDL models on the following criteria: Akaike criterion (AIC) (Akaike 1981), Bayesian information criterion (BIC) (Watanabe 2013), and the Hannan-Quinn criterion (Mainassara and Kokonendji 2016). It was necessary to evaluate the model with autoregressive terms, taking into account the presence of autocorrelation of errors.…”
Section: Databank Of Thementioning
confidence: 99%
“…The RESET test used one lag, which indicated cointegration between three variables. A measure of the relative quality of the model was assessed using the Akaike criterion (AIC) (Akaike 1981), Bayesian information criterion (BIC) (Watanabe 2013), Hannan-Quinn criterion (Mainassara and Kokonendji 2016), the Engle-Granger cointegration test (Engle and Granger 1987). All tests confirmed the homoscedasticity of the residues (p > 0.05).…”
Section: Databank Of Thementioning
confidence: 99%